Fictionality of Heiner Muller’s Drama: Forms and Functions - N. E. Seibel (Научный диалог)
Using the broad material of Heiner Müller’s drama (1929-1995), the question of how to destroy the classical forms of dramatic conventions in German drama of the 60-80s is discussed in the article. The author dwells on the repeatedly criticized and revised discussion that unfolds around the concept, appeared at the end of the 20th century of post-drama H. T. Lehman theater. The author of the article adheres to the point of view that the importance of post-drama as an experimental site of the latest theater can hardly be overestimated. The general laws of constructing a figurative system, a chronotope and a composition of Müller plays are analyzed. The researcher comes to conclusions about how deliberate fantasy and fictionality contribute to the implementation of the author’s attitude towards journalism and ideology. Particular attention is paid to intertextuality, provocativeness, collage. H. Muller’s experiments are aimed at updating the political drama and forcing directors and spectators to clearly define their own political position. The playwright’s mindset to combine recognizable fragments - either they are Shakespearean characters or historical situations - into an unpredictably paradoxical entire that allows the viewer to form an analytically balanced position on topical issues is examined in detail. The novelty of the study is to systematize and build a hierarchy of the main dramatic experiments used by the researched author.